2021
DOI: 10.3389/fmars.2021.702570
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Plastic Beach Litter by Number or by Weight: The Implications of Fragmentation

Abstract: Eighty surveys of ten Scottish beaches recorded litter sizes and weights. A simple model of fragmentation explains the distribution of plastic beach litter weights, producing a logarithmic cascade in weight-frequencies having a power law exponent of 1.6. Implications of fragmentation are numerous. Heavy litter is rare, light fragments are common. Monitoring by number is sensitive to minimum observable fragment size, age of the litter, and energy of the foreshore. Mean litter item weights should be used to calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
(70 reference statements)
2
14
0
Order By: Relevance
“…Originating from sources both on land and at sea, beached litter can comprise a wide range of materials, including plastic, metal, wood, rubber, glass, and paper (Nelms et al, 2017;Turrell, 2019;Morales-Caselles et al, 2021). Many studies (e.g., Derraik, 2002;Topcu et al, 2013;Nelms et al, 2017;Lebreton and Andrady, 2019;Turrell, 2019;Morales-Caselles et al, 2021;Smith and Turrell, 2021;Damian et al, 2022) have shown that litter composition is dominated by plastic, because of its buoyancy and persistence (Topcu et al, 2013). According to the OSPAR commission (OSPAR, Commission, 2019), up to 90% of the items found on beaches in the OSPAR Maritime Area were plastic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originating from sources both on land and at sea, beached litter can comprise a wide range of materials, including plastic, metal, wood, rubber, glass, and paper (Nelms et al, 2017;Turrell, 2019;Morales-Caselles et al, 2021). Many studies (e.g., Derraik, 2002;Topcu et al, 2013;Nelms et al, 2017;Lebreton and Andrady, 2019;Turrell, 2019;Morales-Caselles et al, 2021;Smith and Turrell, 2021;Damian et al, 2022) have shown that litter composition is dominated by plastic, because of its buoyancy and persistence (Topcu et al, 2013). According to the OSPAR commission (OSPAR, Commission, 2019), up to 90% of the items found on beaches in the OSPAR Maritime Area were plastic.…”
Section: Introductionmentioning
confidence: 99%
“…Once a particle enters the ocean it is exposed to horizontal and vertical advection, diffusion, (e.g., Critchell and Lambrechts, 2016) beaching, and deposition in coastal and benthic sediments (e.g., Zhang, 2017;Turrell, 2018). The variability of deposition is influenced by fluctuating hydrodynamic factors, e.g., the prevalence of offshore/onshore winds, the suspension and resuspension by rising and falling tides (e.g., Turrell, 2018), as well as the impact of in-situ fragmentation (Smith and Turrell, 2021), driven by physical processes such as, currents, wind, Ekman transport and wave-induced Stokes' drift (e.g., Dobler et al, 2019;Onink et al, 2019;. Wind, in particular, could have a significant impact on floating litter transport, and is represented by the intensity of wind drag on the exposed part of a floating object (Onink et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies were based on direct visual analysis in the field (n=9) or a mix of both visual analysis and sample collection (n=7). Although faster, visual analysis tends to underestimate the smaller items in a given area (Smith & Turrell, 2021), being a relevant source of bias in marine litter estimates.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…We verified that 27.1% of the studies reported data as quantities per linear distance (m -1 , km -1 , ha -1 ), which is dependent on the non-steady beach width and thus, comprises a limitation to data comparisons. Furthermore, reporting data in terms of weight.area -1 may demand some special attention, since while lightweight fragments tend to be abundant, heavy and big items are not so common and, when they are present, they can affect total sample weight (Smith & Turrell, 2021).…”
Section: Reporting Methodsmentioning
confidence: 99%
See 1 more Smart Citation